«… А terrible anathema is roaring» (riddles of one of Ahmatova’s octastich) - Казарин, Владимир Павлович; Новикова, Марина Алексеевна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The paper examins the unpublished (within her life) verse by Anna A. Akhmatova (1959). It is one of the late poet’s reflections on the ill-famed Soviet Communist Party’s Central Committee Resolution (1946). This document contained pogrom-like criticism of Akhmatova’s and Zoschenko’s literary practice. It had not been denounced up to 1988. Thus, Akhmatova’s key symbol «anathema» and references «Libava (now Liepaja, former Libau)» and «Vladivostok» are commented in historical, social and literary contexts.